DIGITAL TRANSFORMATION OF WEB-BASED ACCOUNTING INFORMATION SYSTEMS FOR THE REVENUE CYCLE IN MULTIPURPOSE COOPERATIVES - Merry Hanif Rahma; Anik Kusmintarti; Kurnia Ekasari (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
Cooperatives in Indonesia play a strategic role in supporting local economic development and community welfare. However, many cooperatives still rely on manual and fragmented financial management processes that hinder efficiency, accuracy, and transparency in reporting. To overcome these challenges, this study aims to design a web-based Accounting Information System (AIS) for the revenue cycle of KPRI Pergu Singosari as a digital solution to overcome these challenges. To overcome these challenges the research adopts a Research and Development (R&D) approach with the Rapid Application Development (RAD) method, which includes needs analysis, system design, prototype development, and conceptual evaluation. Through business process modelling using Data Flow Diagrams (DFD), this study identifies key performance gaps in the cooperative’s manual accounting system particularly data fragmentation, duplicate recording, and delays in financial reporting. The proposed web-based AIS integrates revenue data across multiple business units (savings and loans, retail, transportation, and land plots) into a single centralized database. The output of this research is a conceptual and functional prototype that demonstrates the system’s technical and functional feasibility in supporting real-time reporting and consolidated cooperative Surplus (SHU) preparation. The conceptual evaluation indicates the prototype’s potential to enhance operational efficiency, data accuracy, and transparency in financial management.